Cardiorespiratory response to a 5 hole round in NCAA Division I male golfers - Sutton, P. J.; Ziola, K.; Moore, J.; Alfero, E.; Johnson, Q. R.; Bratton, A.; Hammer, S. M.; Smith, D. B. (International Journal of Golf Science, 2025)
PURPOSE: To determine the cardiorespiratory responses to limited course play in collegiate golfers. METHODS: Six Division I men`s golfers completed a peak exercise test and on a separate testing day, cardiorespiratory response was monitored whilst completing the first 5 holes of a round of golf. For each variable, data were expressed as a percentage of the peak response during the maximal test and categorized by relative quartiles (Q1-4). RESULTS: On average, the relative VO2 (76% of time) and absolute VO2 (74% of time) response to the 5-hole round was in Q2. Furthermore, 64% of time was in Q3 for breathing frequency, and 49% of time was in Q2 for tidal volume. Ventilation was predominantly in Q2, with 62% of time spent. Heart rate predominated Q3 (82% of the time). PRACTICAL APPLICATIONS: Cardiorespiratory responses do not consistently exceed 50% of aerobic capacity, however, specific measures may be useful for on-course monitoring.